Current Advances in Triple-Negative Breast Cancer (TNBC) Chemotherapy: A Literature Review - Murwanti, Retno; Rommy; Nugroho, Agung Endro (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Triple-negative breast cancer (TNBC) is one of subtypes of cancer with the most associated death. With more than 20% of breast cancer patients having this subtype, an effective and safe chemotherapy is needed to ensure complete pathomorphological response. Currently, therapies for TNBC patients are divided into systemic therapy regimens for operable or non-operable diseases, with non-operable diseases mostly treated with targeted therapies such as pembrolizumab in tandem with other chemotherapy agents such as paclitaxel, gemcitabine or carboplatin. TNBC patients whom tumor is operable underwent additional step such as preoperative systemic therapy, which offers several advantages than chemotherapy alone. Neoadjuvant chemotherapy (NACT), which consist of mainly drugs from therapeutic classes such as anthracycline and taxanes, is used with limited success (23%) and decreased recurrence rates. Optimal method for treating TNBC is still lacking, therefore the need for further research regarding chemotherapy for TNBC with higher success rate and better prognosis for the patients is paramount.